Adapting Flat Design Concept in Digital Graphics to Wayfinding Signage Development: Redirecting Movement and Recreating the Environment - Siyanbola, Afeez Babatunde; Oladesu, Johnson O.; Afolabi, Benjamin Eni-itan F.; Uzzi, Festus O. (VCD: Journal of Visual Communication Design, 2023)
People visiting built environments are desirous of accomplishing their aim of visiting such place within the shortest possible time, devoid of negative feelings/ spatial anxiety. Meanwhile, some environment such as hospital, academic setting among others are known for complex structures whereby navigation can become daunting especially when characterised by poor wayfinding system. This therefore necessitated a study on development of wayfinding signage adapting flat design which ordinarily was a design concept invented for digital screens. Innovatively, the wayfinding system was printed for Fine and Applied Arts Building, Olabisi Onabanjo University, Ibogun Campus, relying also on colour psychology, typography, shape and user experience. Research method adopted for the study was mixed method: experimental and survey. User perception of the wayfinding system was sampled using questionnaire administered to 313 respondents. After thorough analysis, results indicated there is consistency in the interior and exterior signage colours, signage textual information are bold and descriptive. The wayfinding system with its shapes added better aesthetic to the environment. This study succeeded in demonstrating how creativity can be put into practise. Thus, recommended that Visual designers (especially in Africa) should be open to new and diverse design concepts for effective visual solution.